Análise da diversificação produtiva da silvicultura em propriedade rural - Mendes, Diogo (2014)
The study addresses the forestry in rural areas and its application in a property located in the municipality of Santa Helena, Parana. The aim was to present the study of forestry, diversification of production and its relevance to the improvement of family income, identifying opportunities and pointing out the difficulties of implementation of forestry in small farms. To the study, through literature review, we identified the increase in forestry activities in the country in recent years, there has been the marketing and the consumer of the same market; addition of plant species more likely arbóraeas for such an undertaking in the western region of Paraná, and any costs of implementation, development, extraction and transportation of the product. Still, we tried to identify the benefits that forestry provides to the environment and society. Finally, we applied the questionnaire to five farmers in the west of Paraná that operate in this sector, in order to identify what methods are used and details of the experience of this practice.